DISEASE MODIFYING THERAPY AND OUTCOME OF RHEUMATOID ARTHRITIS: RETROSPECTIVE ASSESSMENT OF LONG-TERM RESULTS - D. E. Karateyev; M M Ivanova (Научно-практическая ревматология)
Aim of study: To investigate the relation between patterns of basic treatment and the outcome of disease in patients with rheumatoid arthritis (RA). Material and methods: We studied retrospectively two groups of patients with RA (1987 ACR criteria): 1) main group - died (72 patients, mean duration of disease from the onset to death 12.8±0.9 years); 2) control group - alive to 1999 with duration of disease at least 15 years (90 patients, mean follow-up period 19.4±0.47 years). Results: Some patterns of basic treatment were observed: 1) "passive ” strategy - only hydroxychloroquine or sulphasalazine during many years; 2) "inteirupted " treatment - early treatment gold or cytotoxics, but when improvement occurred, therapy with DMARD was interrupted for 1-2 years or more, after that re-started etc.; 3) “emergency” strategy’ - 7-10years of "passive" treatment, after that se\>ere destruction and/or amyloidosis appeared, and cytotoxics started; 4) typical "pyramid " strategy; 5) "active " strategy - early start of treatment with active DMARD (melotrexate, gold) with consecutive change of DMARDs without interruption of basic treatment (very close to "sawtooth ” strategy). The most of died patients were treated with "passive ” and "interrupted" strategies, but the most of patients in control group were treated with "pyramid” and "active" strategies. Conclusion: active strategy of basic treatment has a positive influence on the survival ofpatients with R.A.